M2 receptor activation inhibits cell cycle progression and survival in human glioblastoma cells. Issue 4 (14th March 2013) - Ferretti, Michela; Fabbiano, Cinzia; Bari, Maria Di; Conte, Claudia; Castigli, Emilia; Sciaccaluga, Miriam; Ponti, Donatella; Ruggieri, Paola; Raco, Antonino; Ricordy, Ruggero; Calogero, Antonella; Tata, Ada Maria
Abstract Muscarinic receptors, expressed in several primary and metastatic tumours, appear to be implicated in their growth and propagation. In this work we have demonstrated that M2 muscarinic receptors are expressed in glioblastoma human specimens and in glioblastoma cell lines. Moreover, we have characterized the effects of the M2 agonist arecaidine on cell growth and survival both in two different glioblastoma cell lines (U251MG and U87MG) and in primary cultures obtained from different human biopsies. Cell growth analysis has demonstrated that the M2 agonist arecaidine strongly decreased cell proliferation in both glioma cell lines and primary cultures. This effect was dose and time dependent. FACS analysis has confirmed cell cycle arrest at G1/S and at G2/M phase in U87 cells and U251 respectively. Cell viability analysis has also shown that arecaidine induced severe apoptosis, especially in U251 cells. Chemosensitivity assays have, moreover, shown arecaidine and temozolomide similar effects on glioma cell lines, although IC50 value for arecaidine was significantly lower than temozolomide. In conclusion, we report for the first time that M2 receptor activation has a relevant role in the inhibition of glioma cell growth and survival, suggesting that M2 may be a new interesting therapeutic target to investigate for glioblastoma therapy.